Prognostic value of miR-106a and miR-20a in AML patients with chemotherapy or allo-HSCT treatment - Yue Liu; Jiayu Liu; Yuehua Feng; Xiaoguang Xu; Yingjie Miao; Huijuan Chen; Yu Zhou; Yijun Pan; Yan Liu; Weiying Gu; Yang Cao (Hematology)
Background: MiR-106a and miR-20a (miR-17 family members) are frequently dysregulated in carcinogenesis, but their prognostic significance in acute myeloid leukemia (AML) remains unclear.Methods: We analyzed miR-106a and miR-20a expression in bone marrow from 115 AML patients and 45 healthy controls using qRT-PCR. Additionally, we utilized TCGA data (n=188) to assess the association of these miRNAs with clinical factors and outcomes. Prognostic analysis evaluated the impact of miR-106a and miR-20a on overall survival (OS) and event-free survival (EFS). Differentially expressed genes (DEGs) were identified using Limma. GO and KEGG pathway analyses were performed by DAVID. GSEA and PPI were constructed using ClusterProfiler and STRING database.Results: MiR-106a and miR-20a elevated in AML versus healthy controls. In chemotherapy group, miR-106ahigh or miR-20ahigh predicted poor OS and EFS, with dual-high expression conferring the worst outcome. In allo-HSCT group, miR-106ahigh or miR-20ahigh predicted poor OS but similar EFS, with dual-high cases showing the worst OS. In the miR-106ahigh or miR-20ahigh group, allo-HSCT prolonged OS (but not EFS) versus chemotherapy. In the miR-106alow or miR-20alow group, there were no obvious differences in OS or EFS between the chemotherapy and allo-HSCT regimens. Multivariable analyses confirmed miR-106a/miR-20a signature as an independent prognostic marker. Moreover, we identified 706 signature-associated DEGs. Bioinformatic analysis illuminated the involvement of miR-106a and miR-20a in regulating diverse biological processes and signaling pathways.Conclusions: MiR-106a and miR-20a are promising AML prognostic biomarkers for adverse outcome. The combined signature improves risk stratification and guides therapy selection (e.g., ⁣allo-HSCT for high-risk cases).